Cementoblastoma of the Mandible: A Case Report and Review of Literature - Seifi, Safoura; Kiani, Marjan; Babaei Darzi, Alireza; Ghorbani, Hakimeh (Journal of Dental School, 2019)
Objectives Cementoblastoma is a rare benign odontogenic tumor which is linked to the root of a vital tooth. This tumor is usually accompanied by pain and swelling, and its most common site is the left mandibular first molar. General dentists’ inattention to oral lesions, especially tooth-related radiopacities, is problematic in some cases and results in delayed or missed diagnosis. Case Our patient was a 31-year-old woman who presented to our clinic complaining of dull pain in the left mandibular first molar. Root canal therapy was performed for the patient but the pain continued for the next 2 years. The patient was referred to a surgeon. Panoramic radiography revealed a radiopaque mass of approximately 2 x 1 cm in diameter attached to the root of the mandibular left first molar. The lesion together with the involved tooth was removed by excisional biopsy. Histopathological diagnosis was cementoblastoma. Conclusion Dentists’ knowledge of pulpal, periapical and periodontal lesions is usually satisfactory, but their inattention to oral lesions, especially tooth-related radiopaque lesions, is problematic in some cases. Pain from cementoblastoma may be mistaken for endodontic pain.